INTEGRASI MAQĀṢID KLASIK DAN KONTEMPORER DALAM PELAYANAN HAJI UNTUK LANSIA, DIFABEL, DAN JEMAAH RISIKO TINGGI: STUDI MAQĀṢID PERSPEKTIF IBN ‘ĀSHŪR DAN JASSER AUDA - Didin Chonyta; Mohammad Jainuri (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
The phenomenon of increasing numbers of elderly, disabled, and high-risk pilgrims poses new challenges for the organization of the Hajj in Indonesia. This situation requires a more adaptive and responsive fiqh approach to the physical and health limitations of pilgrims, as well as an inclusive Hajj service design. This study aims to explore the integration of classical and contemporary maqāṣid al-syarī‘ah in Hajj services for vulnerable groups, through an analysis of the thoughts of Ibn ‘Āshūr and Jasser Auda. The method used is qualitative with a library research approach, focusing on content analysis of the works of Ibn ‘Āshūr (Maqāṣid al-Syarī‘ah al-Islāmiyyah) and Jasser Auda (Maqasid al-Shariah as Philosophy of Islamic Law), as well as a synthesis of the two. This study found that Ibn ‘Āshūr’s version of maqāṣid emphasizes the importance of protecting human life and dignity (ḥifẓ al-nafs and karāmah), while Auda offers a multidimensional, systemic, and contextual approach to maqāṣid. The integration of the two provides a basis for the development of Hajj policies and services that are convenient, safe, and in accordance with the principles of Sharia. The research results confirm that maqāṣid-based Hajj services are not only legally valid but also part of contemporary ijtihad that emphasizes the values of rahmah, ease (taysīr), and spiritual justice. Thus, maqāṣid al-syarī‘ah can serve as a transformative paradigm in designing Hajj services that are friendly to the elderly, people with disabilities, and high-risk pilgrims.